2022
DOI: 10.1590/1414-431x2022e12522
|View full text |Cite
|
Sign up to set email alerts
|

Could paraprobiotics be a safer alternative to probiotics for managing cancer chemotherapy-induced gastrointestinal toxicities?

Abstract: Clinical oncology has shown outstanding progress improving patient survival due to the incorporation of new drugs. However, treatment success may be reduced by the emergency of dose-limiting side effects, such as intestinal mucositis and diarrhea. Mucositis and diarrhea management is symptomatic, and there is no preventive therapy. Bacterial and fungal-based compounds have been suggested as an alternative for preventing the development of diarrhea in cancer patients. Using probiotics is safe and effective in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…33 However, despite the proven positive regulatory effects of LGG on intestinal microecology, clinical trials have also found that long-term consumption of live LGG in immunocompromised populations may lead to adverse reactions, such as bacteremia. 50,51 In this study, we identified that oral administration of LGG-EV can synergistically improve the therapeutic effect of anti-PD-1 inhibitors. We demonstrated that oral LGG-EV enhanced lymphocyte infiltration in tumor tissues, including antigen-presenting dendritic cells and CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 95%
“…33 However, despite the proven positive regulatory effects of LGG on intestinal microecology, clinical trials have also found that long-term consumption of live LGG in immunocompromised populations may lead to adverse reactions, such as bacteremia. 50,51 In this study, we identified that oral administration of LGG-EV can synergistically improve the therapeutic effect of anti-PD-1 inhibitors. We demonstrated that oral LGG-EV enhanced lymphocyte infiltration in tumor tissues, including antigen-presenting dendritic cells and CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 95%
“…Other adverse effects, such as oral mucositis, constipation, and diarrhea, are also associated with dysgeusia. The painful lesions of oral mucositis, in addition to interfering with food intake, are often secondarily colonized by bacteria and fungi ( 28 ) leading to dysbiosis in addition to interfering with the taste of food ( 29 ) modifies the microbiota of the rest of the gastrointestinal tract leading to changes in motility (constipation and diarrhea) ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…These concerns would apply also to synbiotics and probiotic mixtures. In contrast, postbiotics or paraprobiotics, which are not live bacteria, would be less likely to cause harm to immunocompromised patients [23].…”
Section: Probiotic Mixturesmentioning
confidence: 99%
“…Table 1. Definitions of the different relevant terms related to the use of probiotics and probiotic-related derivatives [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%